Teaching Peace, Stopping Bullying: The Transformative Power of KH Ahmad Dahlan’s Psychoeducation - Saputra, Wahyu Nanda Eka; Mahira, Anya Ahda; Djajuli, Salsa Puspita Dwi (citeus, 2026)
Bullying in schools remains a serious problem that negatively impacts students' academic and psychological development. A safe and violence-free learning environment is crucial to supporting the achievement of national education goals, thus requiring effective interventions to reduce bullying behavior. This study aims to test the effectiveness of group counseling services using psychoeducational techniques based on the teachings of KH. Ahmad Dahlan in reducing bullying behavior. The scope of the study focuses on the application of peaceful values in junior high schools as a prevention strategy and as a positive character development strategy for students. This study used a quantitative approach with a quasi-experimental non-equivalent control group design. The subjects were 14 students from Muhammadiyah Bantul Junior High School identified as having high levels of bullying. They were divided into an experimental group that received psychoeducational intervention and a control group with no treatment. The results showed a significant decrease in the experimental group's bullying scores after participating in five sessions of peaceful psychoeducation, from an average pretest of 97.1 to 59.4 on the posttest. In contrast, the control group experienced no significant changes, thus proving the effectiveness of the intervention. This study concludes that psychoeducation based on the teachings of KH. Ahmad Dahlan is effective in suppressing bullying behavior while fostering empathy and social awareness in students. These findings provide practical contributions to school guidance and counseling services and provide recommendations for integrating local wisdom values into bullying prevention strategies.